The value relevance of top executive departures: Evidence from the Netherlands - Cools, Kees; Mirjam van Praag, C. (Journal of Corporate Finance, 2007)
On theoretical grounds, monitoring of top executives by the (supervisory) board is expected to be value relevant. The empirical evidence is ambiguous and we analyze three non-competing explanations for this ambiguity: (i) The positive effect on firm value of board monitoring is hidden in stock price effects due to the simultaneous occurrence of the positive real effect of monitoring and the opposing information effect. (ii) The combination of board monitoring and monitoring by other parties prevents assessing the value relevance of board monitoring in isolation. (iii) The confounding effect of a simultaneous successor appointment typically generates an upward biased estimate. Based on an analysis of price effects and trading volumes at announcement, we conclude that monitoring by the supervisory board is valued by investors: Forced departures of executive directors, also without a successor appointment, are value relevant in the Netherlands where external control mechanisms and shareholder control were virtually absent in the period studied (1991–2000).